2013
DOI: 10.1149/05049.0153ecst
|View full text |Cite
|
Sign up to set email alerts
|

High Efficiency CuCl Electrolyzer for Cu-Cl Thermochemical Cycle

Abstract: The Cu-Cl thermochemical cycle is a promising technology for hydrogen production due to moderate temperature requirements and compatibility with commercially demonstrated renewable heat sources, such as the solar power tower. CuCl/HCl electrolysis, the main hydrogen-producing step of the cycle, has been investigated using a newly developed electrolyzer system supplemented by a number of electrochemical characterization techniques. Nafion- based membranes and Pt/C catalysts were used to prepare membrane electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“…The two catalyst application techniques reviewed were the painted loading technique used previously 14,15 and the sprayed painting technique. The resulting SEM image for a brush painted electrode is displayed in Figure 12 (right) and sprayed in Figure 12 (left).…”
Section: Resultsmentioning
confidence: 99%
“…The two catalyst application techniques reviewed were the painted loading technique used previously 14,15 and the sprayed painting technique. The resulting SEM image for a brush painted electrode is displayed in Figure 12 (right) and sprayed in Figure 12 (left).…”
Section: Resultsmentioning
confidence: 99%
“…Canada Nuclear Laboratories (formerly Atomic Energy of Canada Limited) demonstrated hydrogen production by a CuCl electrolyzer continuously for several days and reported that electrolysis is feasible at low potentials (0.6‐0.7 V) at a current density of 0.1 A cm −2 using inexpensive materials . The Pennsylvania State University has carried out comprehensive experiments and theoretical developments on the cycle . Balashov et al performed an experimental study on a CuCl/HCl electrolyzer and reported a voltage efficiency of 80% and a current efficiency of 98%, which is with a good agreement with Faraday law.…”
Section: Introductionmentioning
confidence: 83%
“…6 The membrane was pretreated by the following steps to remove the organic and inorganic contaminants before being used in the electrolyzer. First, the membrane was soaked in 3 wt% H 2 O 2 solution at 80…”
Section: Methodsmentioning
confidence: 99%
“…A significant increase in the cell performance was observed as the temperature was increased from 40 to 80 • The Cu-Cl thermochemical cycle is among the most attractive technologies proposed for hydrogen production, 1-4 and significant improvements in the current and voltage efficiencies of the CuCl(aq)/HCl(aq) electrolytic cell -a key component in the cycle -have recently been reported. [5][6][7] In our previous work, 7 kinetic properties of the CuCl electrolyzer were investigated to successfully reduce the catalyst loading by 68% without causing any adverse effect on the cell performance and durability of the cell was reported for 168 h of operation. …”
mentioning
confidence: 99%
See 1 more Smart Citation